One piece. Vol. 6, The oath - Oda, Eiichiro, 1975-; Amemiya, Naoko; Caselman, Lance (San Francisco : Viz, 2005)
Luffy sets his sights on Sanji as their new cook; but it will take more than a little sweet talk to get him to join Luffy's team.
"This book reads from right to left"--Cover page [4].
"This graphic novel contains material that was originally published in English in Shonen Jump #23-25"--Page facing t.p.
Translated from the Japanese.
Adult
Adult
Keywords: Pirates -- Fiction; Treasure troves -- Fiction; Buried treasure -- Fiction; Comic books, strips, etc; Pirates -- Fiction; Adventure fiction; Graphic novels